2002
DOI: 10.1046/j.1365-2583.2002.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids in SRS1 and SRS6 are critical for furanocoumarin metabolism by CYP6B1v1, a cytochrome P450 monooxygenase

Abstract: CYP6B1v1 is the principal cytochrome P450 monooxygenase (P450) that detoxifies dietary furanocoumarins in the guts of Papilio polyxenes, the black swallowtail caterpillar. Sequence alignments and structure comparisons of CYP6B1v1 with the mouse CYP2A5 and bacterial CYP102 proteins, which are also capable of metabolizing the linear furanocoumarin xanthotoxin (8-methoxypsoralen), suggested that Phe116, His117, Val368 and Phe484 might be active site residues. In a homology model developed for CYP6B1v1, the side c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 57 publications
0
54
0
Order By: Relevance
“…Of the two P. canadensis proteins, CYP6B25, an in-group homologue to CYP6B4 (17), generated a major CO-difference peak at 450 nm and a minor peak at 420 nm and CYP6B26, an in-group homologue to CYP6B17 and seven amino acids shorter at its C terminus (16), generated a CO-difference peak only at 420 nm (P420 form), indicating that this enzyme is incorrectly folded. Molecular modeling and site-directed mutagenesis presented in Chen et al (20) have indicated that aromatic residues F116, H117, and F484 positions are required for correct folding of the P. polyxenes CYP6B1 enzyme, and that two of these modulate the range of furanocoumarins metabolized. This seems not to be the case for P. glaucus͞P.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the two P. canadensis proteins, CYP6B25, an in-group homologue to CYP6B4 (17), generated a major CO-difference peak at 450 nm and a minor peak at 420 nm and CYP6B26, an in-group homologue to CYP6B17 and seven amino acids shorter at its C terminus (16), generated a CO-difference peak only at 420 nm (P420 form), indicating that this enzyme is incorrectly folded. Molecular modeling and site-directed mutagenesis presented in Chen et al (20) have indicated that aromatic residues F116, H117, and F484 positions are required for correct folding of the P. polyxenes CYP6B1 enzyme, and that two of these modulate the range of furanocoumarins metabolized. This seems not to be the case for P. glaucus͞P.…”
Section: Resultsmentioning
confidence: 99%
“…In this latter protein, an aromatic network that involves residues Phe-116, His-117, Phe-484, and Phe-371 is critical for substrate binding affinity to the CYP6B1 active site (20,33). Three-dimensional models of the present day CYP6B4 and the ancestral Anc1 and Anc2 proteins that we have con- 3.…”
Section: Phylogeny Of Cyp6b Genes and Reconstruction Of Ancestral Cyp6bmentioning
confidence: 88%
“…A molecular model of CYP6AB3v1 contains three-dimensional elements similar to those predicted in the catalytic sites of the furanocoumarin-metabolizing CYP6B proteins in P. polyxenes, P. glaucus, and H. zea (25)(26)(27)31) including residues in the B-helix and BЈ-C loop of SRS1, the I-helix of SRS4, and the ␤-turn in ␤-sheet 4 of SRS6 (30). Amino acids are also conserved in SRS1, SRS4, and SRS5 that contribute to form the catalytic site of CYP6B1 from the specialist P. polyxenes, CYP6B4 from the generalist P. (25,31,32).…”
Section: Much Of What Is Known Of Allelic Variation In Insect P450smentioning
confidence: 98%
“…Furanocoumarin-metabolizing P450s of polyphagous (generalist) species, such as H. zea and P. glaucus, catalyze metabolism of a wide range of furanocoumarins with lower activities than the P450s of specialist species, such as P. polyxenes, which feed exclusively on furanocoumarin-containing host plants (17,20,(25)(26)(27)(28)(29). Molecular modelings of these P450s have indicated that at least some of the P450s in generalist insects are structurally more flexible and capable of binding a more diverse array of compounds when compared with some of the P450s in specialist insects (26,27).…”
Section: Much Of What Is Known Of Allelic Variation In Insect P450smentioning
confidence: 99%
“…Insect P450s capable of metabolizing allelochemicals have been identified (30,31). For example, CYP6B1v1 and CYP6B3v1 from the black swallowtail butterfly, Papilio polyxenes, can metabolize the furanocoumarins it is exposed to in its diet (32,33). Numerous individual P450s have also been implicated in insecticide resistance in different insect populations (34)(35)(36)(37)(38).…”
mentioning
confidence: 99%